2018
DOI: 10.1038/s41598-018-20198-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent inner ear specialization for high-speed hunting in cheetahs

Abstract: The cheetah, Acinonyx jubatus, is the fastest living land mammal. Because of its specialized hunting strategy, this species evolved a series of specialized morphological and functional body features to increase its exceptional predatory performance during high-speed hunting. Using high-resolution X-ray computed micro-tomography (μCT), we provide the first analyses of the size and shape of the vestibular system of the inner ear in cats, an organ essential for maintaining body balance and adapting head posture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…To achieve this, cheetahs exhibit a modified morphology compared to other felids, having elongated hind legs and spine, an aerodynamic skull, semiretractable claws, and enhanced metabolic and adrenal systems (Hudson et al, 2010(Hudson et al, , 2011Russell & Bryant, 2001). Further, the cheetah's specialized vestibular system is larger than that of other felids, allowing it to maintain postural stability and balance during prey pursuits (Grohé, Lee, & Flynn, 2018). The cheetah has evolved to prioritize acceleration and agility over the pouncing behavior characteristic of Panthera (Kleiman & Eisenberg, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, cheetahs exhibit a modified morphology compared to other felids, having elongated hind legs and spine, an aerodynamic skull, semiretractable claws, and enhanced metabolic and adrenal systems (Hudson et al, 2010(Hudson et al, , 2011Russell & Bryant, 2001). Further, the cheetah's specialized vestibular system is larger than that of other felids, allowing it to maintain postural stability and balance during prey pursuits (Grohé, Lee, & Flynn, 2018). The cheetah has evolved to prioritize acceleration and agility over the pouncing behavior characteristic of Panthera (Kleiman & Eisenberg, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Early development of the inner ear largely before birth may partly explain its strong link to phylogeny 16 18 . In addition, intraspecific variability of this structure is lower than the inter-genera disparity giving solid grounds to its use in systematics and phylogeny 19 21 . While molecular data help us understand the relationships of living taxa, the search for pertinent morphological characters is critical to our understanding of the origin and divergence of clades.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have related vestibular system enlargement and SC elongation to higher sensitivity and differences in lifestyle. For instance, Grohé et al (2018) found that the vestibular systems of cheetahs (Acinonyx jubatus) differ strongly in shape and proportions (larger vestibular systems, longer SCs, ASC less extended anteriorly, PSC and LSC extended dorsally) from those of other cat species (including a closely related extinct cheetah species). They consider this to be an adaptation to the species' specialized high-speed hunting strategy.…”
Section: Discussion the Effect Of Microhabitatmentioning
confidence: 99%
“…Considering the above, and bearing in mind the anatomical complexity of the vestibular system, clearly not only the size of the semicircular canals, but also their shape can influence the system's sensitivity and response time to head motion. The shape of the vestibular system has been studied in several taxa, both extant and extinct, and was often linked to microhabitat structure, locomotor style (terrestrial vs. arboreal, swimming vs. walking, bipedal vs. quadrupedal) and phylogeny (Spoor et al, 2002;Maddin & Sherratt, 2014;Billet et al, 2015;Pfaff et al, 2015;Grohé et al, 2016;Mennecart et al, 2017;Dickson et al, 2017;Le Maitre et al, 2017;Loza et al, 2017;Palci et al, 2017;Boyle & Herel, 2018;Grohé et al, 2018). It is generally suggested by previous studies that species which are more agile and more sensitive to motion possess longer and relatively circular canals.…”
Section: Introductionmentioning
confidence: 99%